Monitoring Dan Evaluasi Rencana Induk Kemajuan Ilmu Pengetahuan Dan Teknologi Kota Surakarta Tahun 2021-2025 - Bayu Harjono; Pratiwi Dwihapsari; Agus Tri Hananto; Ulul Albab (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The rapid development and progress of science and technology (IPTEK) has had a positive impact on increasingly sophisticated science and technology and supports the creation of new technologies. Technological progress produces modernity, which is characterized by economic growth, social mobility, cultural expansion or expansion. The development of science and technology requires people to increase their competence, so that they can balance with today's modern times. The progress of science and technology is the beginning of a country's success, because it can create something new and can make work easier.